A comparison between Singaporeans and western expatriates of attitudes towards quarantine and preventive measures during a pandemic. - Leong, Connie Si Min. (2011)
The history of influenza pandemic indicates the fatal impact of it on the human population. During an outbreak, cooperation and compliance towards public interventions is essential. In this study, constructs of the Individualism and Collectivism and ingroup-outgroup relationships were used to explore the cross cultural differences between Singaporeans and Western expatriates in their response during a hypothetical pandemic. Attitudes and behaviors, namely motivation towards quarantine and the willingness to practice preventive measures were explored. Survey results collected support the hypothesis that Singaporeans were most concerned about protecting their family, while Western expatriates were most concerned about protecting other people in the community. Willingness to practice preventive measures were also found to be rated higher among Singaporean participants.